Vulnerabilities in coronavirus glycan shields despite extensive glycosylation - Yasunori Watanabe (Nature Portfolio, 2020)
Glycosylation plays a key role in shielding of immunogenic epitopes on viral spike (S) proteins. Here Watanabe et al. report that glycans of coronavirus SARS and MERS S proteins are heterogeneously distributed and do not form an efficacious high-density global shield which would ensure efficient immune evasion.